Penyusunan Konsep Desa Wisata sebagai Acuan Rencana Pengembangan Desa Wisata Ranuyoso, Kabupaten Lumajang - Fredy Nugroho Setiawan; Rizki Nufiarni; Sri Utami Budi; Arcci Tusita (Universitas Muhammadiyah Semarang, 2022)
Ranuyoso is one of the villages in Lumajang Regency which has the potential to become a tourism village. This potential is supported by the existence of an 8 (eight) hectare unused land owned by Perhutani, whose management rights are handed over to villagers, but its utilization has not been maximized to support the program for establishing a tourism village. Therefore, this community service program is the first step towards realizing the development of Ranuyoso as a tourism village. The activity carried out is in the form of data collection as a reference for mapping the concept of the Ranuyoso tourism village. By applying the principles of Community Based Tourism (CBT), this activity involves the active role of villagers in Focus Group Discussions (FGD), interview, and field observation. The results of this activity show that Ranuyoso village has several potentials in the form of hills, springs, fruits, and distinctive arts and culture that can be developed as assets of a tourism village. These potentials are the basis for formulating the concept of Ranuyoso tourism village, namely a tourism village that presents the integration of water tourism, culture and arts tourism, fruit tourism, and adventure tourism. In addition, this activity also resulted in a draft of cooperation agreement between Faculty of Cultural Studies Universitas Brawijaya (FCS UB) and Forest Village Community Institution (LMDH) as a legal basis for discussing cooperation related to the development of Ranuyoso..